Why do orthopedic implants break?: A retrospective analysis of implant failures at a rural tertiary care centre in central India - Rohan R Patil; Chandrashekhar M Badole; Girish B Mote; Kiran N Wandile (Wolters Kluwer Medknow Publications, 2020)
Background: The AO Foundation's Association for the Study of Internal Fixation has advocated rigid fixation with implants in the form of plates and screws. Focus is on development of implants which are stronger, more acceptable to the body, cheaper, and durable. Aim: The aim of this study was to find the factors responsible for implant breakage. Materials and Methods: We have retrospectively analyzed the data from January 2008 to December 2018 (10 years). Information on sociodemographic characteristics, clinical features, and radiographic features was retrieved from the hospital information system. Data were entered and analyzed with Epi Info software. Results: Of the 37 patients, there were 33 (89.2%) males and four (10.8%) females in the age group of 17-95 years. The most common site for implant breaks was observed to be the shaft of the femur (40.5%), and the most common type of implants which broke were locking intramedullary nails (62.1%). Conclusion: The factors responsible for breakage of implants were observed to be: retrauma, failure of compliance with advice about ambulation, absence of union at fracture sites, and persistent infection. Out study shows the importance of educating patients properly about physiotherapy and rehabilitation protocols.